Mystic Acetaldehyde: The Never-Ending Story on Alcoholism - Peana, Alessandra T.; Sánchez-Catalán, María J.; Hipólito, Lucia; Rosas, Michela; Porru, Simona; Bennardini, Federico; Romualdi, Patrizia; Caputi, Francesca F.; Candeletti, Sanzio; Polache, Ana; Granero, Luis; Acquas, Elio (Frontiers in Behavioral Neuroscience, 2017)
After decades of uncertainties and drawbacks, the study on the role and significance of acetaldehyde in the effects of ethanol seemed to have found its main paths. Accordingly, the effects of acetaldehyde, after its systemic or central administration and as obtained following ethanol metabolism, looked as they were extensively characterized. However, almost five years after this research appeared at its highest momentum, the investigations on this topic have been revitalized on at least three main directions: 1) the role and the behavioural significance of acetaldehyde in different phases of ethanol self-administration and in voluntary ethanol consumption; 2) the distinction, in the central effects of ethanol, between those arising from its non-metabolized fraction and those attributable to ethanol-derived acetaldehyde and 3) the role of the acetaldehyde-dopamine condensation product, salsolinol. The present review aims at presenting and discussing prospectively the most recent data accumulated following these three research pathways on this never-ending story in order to offer the most up-to-date synoptic critical view on such still unresolved and exciting topic.